Characterization of Tuna Jerky with the Addition of Seaweed (Eucheuma cottonii) Flour - Reni Lobo; Joko Santoso; Bustami Ibrahim (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Fish jerky has hard texture which could make the appearance became less attractive to consumers. The aim of this study was to characterize tuna jerky with the addition of seaweed flour E. cottonii in order to increase acceptability by consumers. Result shown that seaweed flour characterization was consisted dietary fiber 73.95±0.45%, viscosity 107.02±0.51 cPs, gel strength 435.03±4.99 g/cm2, carageenan 54.56±0.18%, heavy metal Hg was <0.002 ppm, Pb was <0.004 ppm and Cd was 0.063±0.001 ppm, water content 12.63±0.08% and yield 6.07±0.08%. Based on research result, the additional of 2.5% E. cottonii concentration flour resulting high quality jerky with appearance value was 7.60, flavour was 7.67, texture was 5.7 and taste was 7.63 from 1-9 scales. Result from paired comparison test against commercial jerky (beef) resulting positive value, that means the quality of tuna jerky had better quality compared to commercial jerky and well accepted by panelist. Proximate analysis of tuna jerky shown that protein content 30.24±0.1%, water 11.32±0.02%, lipid 3.03±0.00% and ash 5.69±0.06%. Texture analysis results shown hardness 827.50±15.67, adhesiveness 0.09±0.02 and fracture 10.95±2.24.